The rise of hybrid diplomacy: from digital adaptation to digital adoption. (7th March 2022) - Bjola, Corneliu; Manor, Ilan
Abstract : The COVID-19 pandemic has forced diplomats to work online, but how have they adapted and what impact will this have going forward? Drawing on survey results from 105 diplomats, this article argues that diplomacy is about to enter a hybrid phase, in which physical and virtual engagements are expected to integrate, complement and empower each other. Abstract: The COVID-19 pandemic has forced diplomats to embrace virtual platforms and to learn to combine virtual and physical meetings in their work. In this article, we investigate how this process has taken place and with implications for the conduct of diplomacy. Specifically, we ask how diplomats have adapted to the transition to the virtual medium, what lessons have they learned from this, and how these lessons may inform the conduct of diplomacy in the post-pandemic period? We argue that diplomacy is about to enter a new phase, which we call hybrid diplomacy, in which physical and virtual engagements are expected to integrate, complement and empower each other. We begin by distinguishing between digital adaptation, a forced process brought about by external changes, and digital adoption, a strategic decision by diplomats to use specific technologies towards specific goals. Building on the results of a survey disseminated to 105 diplomats during the pandemic, we then examine how diplomats have adapted to the virtual medium and what challenges they see facing as they transition to the post-pandemic phase. While responders largely agree that virtual interactions are not a good substitute for physical diplomacy, we find strong support for the continued mix of virtual and physical meetings. They enable diplomats to maintain working procedures, collaborate with their peers from around the world, and continue negotiations that began offline. We conclude with a discussion of the technological and social factors that may inform the shape of hybrid diplomacy.